2014
DOI: 10.1155/2014/678401
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms Underlying the Role of MicroRNAs in the Chemoresistance of Pancreatic Cancer

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is an extremely severe disease where the mortality and incidence rates are almost identical. This is mainly due to late diagnosis and limited response to current treatments. The tumor macroenvironment/microenvironment have been frequently reported as the major contributors to chemoresistance in PDAC, preventing the drugs from reaching their intended site of action (i.e., the malignant duct cells). However, the recent discovery of microRNAs (miRNAs) has provided new direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 179 publications
2
43
0
Order By: Relevance
“…Chemoresistance is one of the main obstacles that limit the therapeutic effects of drugs, but the mechanisms that contribute to this have not been fully elucidated. Consistent with previous findings [19,20], we found that miR-34a influences the response of PDAC cells to 5-FU. Our study suggests that the loss of miR-34a expression may be associated with the chemoresistance of PDAC tumor cells.…”
Section: Discussionsupporting
confidence: 93%
“…Chemoresistance is one of the main obstacles that limit the therapeutic effects of drugs, but the mechanisms that contribute to this have not been fully elucidated. Consistent with previous findings [19,20], we found that miR-34a influences the response of PDAC cells to 5-FU. Our study suggests that the loss of miR-34a expression may be associated with the chemoresistance of PDAC tumor cells.…”
Section: Discussionsupporting
confidence: 93%
“…In general, miRNAs are composed of 19-25 nucleotides. Science magazine considered the discovery of miRNA to be one of the top ten scientific advancements in 2002and 2003(Garajova et al, 2014Luo et al, 2014). The relationship between miRNAs and tumors was first identified in chronic lymphocytic leukemia (CLL).…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of osteosarcoma, including development and metastasis, involves multiple genes (Garajova et al, 2014;Phuah and Nagoor, 2014). MicroRNAs (miRNAs), which widely exist in animals and plants, are non-coding, small, regulatory RNAs (Orang and Barzegari, 2014;Saadatian et al, 2014) that can negatively regulate gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…Increasingly, previous studies have focused on the inhibitory effects of miRs on cancer and tumors; cyclooxygenase-2 activity was demonstrated to be suppressed by miR-143, preventing gastric cancer growth and inducing the apoptosis of gastric cancer cells (34). Furthermore, miR-145 levels were enhanced by histone deacetylase inhibitors in a Burkitt lymphoma cell line, and the levels of miR-143 were markedly downregulated in samples from patients with Burkitt lymphoma (35).…”
Section: Discussionmentioning
confidence: 99%